Identifikasi Pemenang Tender Pengadaan Barang Menggunakan Metode TOPSIS - Handayani Metha Putri (LPPM STIKOM Tunas Bangsa, 2023)
PTBA UPO is one of the companies that opens tender opportunities for other companies to meet their needs. To facilitate the decision-making process, a Decision Support System is needed. This study aims to assist companies in determining tender winners in the supply of goods with suitable criteria. This study will select one of the companies that bid with the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. Based on the guidebook that has been set by the company, the criteria used in this study are the company's work methods, goods selection system, workforce that meets the requirements and work experience of companies participating in tenders. Companies that meet the criteria and have the highest ranking from the TOPSIS process can become tender winners. This research can be used as input to the implementing committee as a basis for making decisions in selecting the tender winner.